The soul of America the battle for our better angels - Meacham, Jon 1969- (Random House, 2018)
"Pulitzer Prize-winning author Jon Meacham helps us understand the present moment in American politics and life by looking back at critical times in our history when hope overcame division and fear. Our current climate of partisan fury is not new, and in The Soul of America Meacham shows us how what Abraham Lincoln called the "better angels of our nature" have repeatedly won the day. Painting surprising portraits of presidents including, besides Lincoln, Ulysses S. Grant, Theodore Roosevelt, Woodrow Wilson, Franklin D. Roosevelt, Harry S. Truman, Dwight Eisenhower, and Lyndon B. Johnson, and illuminating the courage of such influential citizen activists as Martin Luther King, Jr., early suffragettes Alice Paul and Carrie Chapman Catt, civil rights pioneers Rosa Parks and John Lewis, First Lady Eleanor Roosevelt, and Army-McCarthy hearings lawyer Joseph N. Welch, Meacham brings vividly to life turning points in American history.